2012
DOI: 10.5539/jfr.v1n4p194
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds, Profiles of Virgin Olive Oils Produced In the Eastern Morocco: Oxidative Stability and Sensory Defects

Abstract: Studies on flavor profiles of virgin olive oil (VOO) are becoming more and more numerous. The VOO aromas are determined by a mixture of chemicals in olive oil, which influence its quality. Various studies around the world have shown that the volatile compounds in VOO depend on the climate, cultivation and process.The present work is a first approach to compare volatile profiles of VOO largely produced in eastern of Morocco after 6 months of storage at ambient temperature in darkness. Oxidative stability measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
(71 reference statements)
0
17
0
3
Order By: Relevance
“…The attribution of a sensory note to this compound in the definition of VOO flavor is not clear. In fact, few studies reported the presence of these compounds in VOO without taking their sensory role into consideration (Vichi et al, 2003;Tanouti et al, 2012). Overall, the volatile compounds with higher levels in Koroneiki VOO have mainly a positive correlation with factor 1.…”
Section: Resultsmentioning
confidence: 98%
“…The attribution of a sensory note to this compound in the definition of VOO flavor is not clear. In fact, few studies reported the presence of these compounds in VOO without taking their sensory role into consideration (Vichi et al, 2003;Tanouti et al, 2012). Overall, the volatile compounds with higher levels in Koroneiki VOO have mainly a positive correlation with factor 1.…”
Section: Resultsmentioning
confidence: 98%
“…3-Ethyl-1,5-octadiene (I) was detected Table 3 Volatiles composition (mg 4-methyl-2-pentanone kg −1 oil) expressed as mean values and standard deviations of Oueslati olive oil from young and adult trees at different stages of maturation only at the green maturation stage of olive oils from young trees: the presence of this hydrocarbon could play an important role in the typical flavors of this oil. However, (Z)-2-penten-1-ol, which is among the compounds responsible for the green odor notes of VOO aroma [32], increased significantly during maturation in oil samples from both young and adult trees. Compared to VOO from adult olive trees, VOO from young olive trees were characterized by higher amounts of (Z)-2-penten-1-ol.…”
Section: Volatile Compoundsmentioning
confidence: 96%
“…To the best of our knowledge, this is the first detailed and comprehensive characterization study of volatile compounds (evaluating their use for the geographical classification too) of Moroccan VOOs. Only a recent work characterizing the effect of storage on volatile compounds of eastern Moroccan olive oils (Tanouti, Serghini-Caid, Sindic, Wathelet, & Elamrani, 2012) can be found in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%